Bidirectional relationships between intolerance of uncertainty and generalized anxiety among adolescents: insights from cross-lagged panel network analysis - Haoxian Ye; Yunyi Li; Yike Huang; Yiming Zhang; Jiaxiong Zhang; Jiaqi Wang; Keying Liu; Yuyi Yao; Xinyu Shi; Yijia Liu; Fang Fan (Child and Adolescent Psychiatry and Mental Health)
Abstract Background Intolerance of uncertainty (IU) has received increasing attention for its role in the development and maintenance of generalized anxiety. However, little is known about the temporal and causal relationships between IU and generalized anxiety, particularly in adolescents. Furthermore, much of the existing literature treats IU and generalized anxiety as unidimensional constructs, limiting a detailed understanding of their internal elements and specific symptom interactions. To address the gaps, this study employed a cross-lagged panel network (CLPN) approach to examine the temporal interactions and predictive relationships between IU elements and generalized anxiety symptoms. Methods A sample of 7,434 nonclinical adolescents (mean age = 15.33 years, range = 11–19 years, 50.6% girls) completed the Intolerance of Uncertainty Scale (Short Form) for Children (IUSC-12) and the Generalized Anxiety Disorder Scale (GAD-7) across two waves, six months apart. Data was analyzed using the CLPN approach. Results Bidirectional predictive relationships were found between IU elements and generalized anxiety symptoms, with generalized anxiety symptoms more frequently predicting IU elements. The generalized anxiety symptom named “nervousness” was the strongest predictor of increases in both IU elements and other generalized anxiety symptoms over time, while the IU elements named “frustration” and “work with hindrance” were the strongest predictors of future generalized anxiety symptoms. Conclusions This study provides new insights into the reciprocal relationships between IU and generalized anxiety among adolescents, highlighting the complex interplay between vulnerability and mental health problems. By identifying key IU elements and generalized anxiety symptoms that drive these relationships, the findings contribute to a more nuanced understanding of adolescent psychopathology and inform targeted interventions.